Gender and the Unemployment Insurance Debates in Canada, 1934-1940 - Pierson, Ruth (Labour/Le Travailleur, 1990)
Abstract This article examines the underlying gender assumptions embedded in the political debate surrounding the implementation of an unemployment insurance scheme in Canada. The vision of UI articulated in the proposals for, drafts of, and responses to UI legislation emphasized and further aided in the construction of the gendered complementarily of masculine independence and feminine dependence as well as of the dichotomization of women into either single workers assimilated to the male norm or dependent wives/mothers. Framing much of this debate was the assumption of breadwinning as a male responsibility. Despite evidence to the contrary, participants in this political discourse reinforced the conception of the male worker as the head of household requiring a 'family wage' sufficient to support a wife and children. When UI was finally instituted, though male workers were privileged over female workers, the meagreness of the provision for dependent wives and children revealed the government's lack of commitment to the principle of the 'family wage.'